Pemilihan Pegawai Berprestasi Pada Kantor Pegawai Badan Daerah Dengan Menggunakan Metode SAW - Hanne Lore Br Siagian; Irfan Sudahri Damanik; Dedi Suhendro (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2021)
Management of human resources (HR) from an office do a lot in improving dedication and performance. However, in reality Simple Additive Weigthing (SAW) are carried still not optimal in the implementation of the selection of out standing employees this study aims to determine the assessment process and the selection of out standing employees the system use the method Simple Additive Weigthing (SAW) by using the ctriteria that have been used, namely work Ethincs, Absenteenism, Discipline, Cooperation and Responsible